2009
DOI: 10.1088/0957-4484/21/4/045201
|View full text |Cite
|
Sign up to set email alerts
|

The effect of catalysts and underlayer metals on the properties of PECVD-grown carbon nanostructures

Abstract: The growth behaviors and contact resistances of vertically aligned carbon nanotubes (CNTs) and carbon nanofibers (CNFs) grown on different underlayer metals are investigated. The average diameter, diameter distribution, density, growth rate and contact resistance exhibit strong correlation with the choice of catalyst/underlayer combination. These observations are analyzed in terms of interactions between the catalyst and the underlayer metal. The CNT via test structure has been designed and fabricated to make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…The thick wall shows the stacking cone-like structure without clear concentric cylindrical carbon layers as that for multi-walled carbon nanotubes (MWCNTs). The ratios of the wall to the inner hollow structure are very big and in some literatures the structure was also attributed to carbon nanofiber (CNF)16. Ni catalysts can be observed at the tip of different CNFs in Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The thick wall shows the stacking cone-like structure without clear concentric cylindrical carbon layers as that for multi-walled carbon nanotubes (MWCNTs). The ratios of the wall to the inner hollow structure are very big and in some literatures the structure was also attributed to carbon nanofiber (CNF)16. Ni catalysts can be observed at the tip of different CNFs in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The combination of classical XANES method with a high spatial resolution in STXM provides a unique capability to explore electronic and structural information in carbon nanomaterials891011121314. Here by employing STXM, Fe and Ni residues, the widely used catalyst in the CNT/CNF growth1516, in individual CNT and CNF were imaged with a concurrent identification of their electronic structure. Interestingly, we found that the catalyst may migrate with the growth of CNT (CNF) through the whole CNT (CNF) as tiny clusters or even atomic metal, which provides the direct evidence on the existence of the atomic metal for the ORR6.…”
mentioning
confidence: 99%
“…To prevent intermixing of catalyst and substrate, a conducting buffer layer can be used. In order to have a good adhesion to the catalyst and the interconnect, the right underlayer material with the right thickness must be carefully chosen [15,16]. Most importantly, it is crucial for the diffusion barrier not to react with the catalyst so that the catalyst film can easily form uniform and discrete nanoparticles.…”
Section: Materials Selectionmentioning
confidence: 99%
“…Next, lithography patterning is performed to create the opening for the depositing of Au or Cu metallization by e-beam evaporation. After the first metallization is completed, a second lithography step is performed for the catalyst (used for CNT growth) and its barrier layer required for CNT growth [12][13][14]. The final 4″ wafer is then diced using a dicing machine and is ready for the growth of CNT.…”
Section: Design and Fabrication Of Flip Chip Structure For High-frequmentioning
confidence: 99%